Some Thoughts on Labor and Political Action / Réflexions sur le mouvement ouvrier et l'action politique - Sturmthal, Adolf (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
SummaryThis is an attempt to formulate, at an early stage of a research project, some hypotheses on the relationship between the labor movement and political action.